INVENTORY OF MACROZOOBENHTOS, WATER QUALITY AND SUBSTRATE IN THE MANGROVE ECOSYSTEM, DUMAI CITY, RIAU PROVINCE - Djunaidi Djunaidi; Tyas Dita Pramesthy; Perdana Putra Kelana; Muhammad Nur Arkham; Rangga Bayu Kusuma Haris (Aurelia Journal, 2023)
Macrozoobenthos has an important role in ecological functions in mangrove ecosystems which can be used as bioindicators in aquatic ecosystems. The purpose of this study was to inventory macrozoobenthos, water quality and substrate found at the study site. The method used in this study was the observation transect method of mangrove vegetation measuring 10 x 10 meters in which 5 sub-plots were made in the plot where each sub-plot measuring 1 x 1 meter. Macrozoobenthos samples were taken from the substrate, stems and roots of mangroves. Measurements of water quality parameters were taken in situ at each research station and the substrate was taken using a shovel and then observed for sediment particles in the Dumai Maritime and Fisheries Polytechnic laboratory. This study succeeded in infentarizing the macrozoobenthos of the Mollusc Phylum, class Gastropods with 6 families and 6 species (Nerita articulata, Chicoreus capucinus, Littorina scabra, Ellobium aurisjudae, Cerithidae quoyii and Pugilina cochlidium) and class Bivalvia, 1 family and 1 species (Polymesoda bengalensis). Water quality parameter values consist of an average temperature of 29.73 ˚C, a salinity of 26.33 ppt, dissolved oxygen (DO) 4.92 mg/l and a pH of 6.9. This water quality condition can still be tolerated by mangrove and macrozoobenthos plants. Substrate texture at stations 1 and 2 includes the clay loam category and station 3 the sandy loam category which has an influence on the abundance of macrozoobenthos.